Application of theory of constraints to foster the services of Indian power transmission system. Issue 3 (8th January 2020) - Upreti, Naveen; Sunder, Raju G.; Dalei, Narendra N.; Garg, Sandeep
Abstract : Purpose: This paper aims to present a practical and sequential application of the theory of constraints (TOC) to eliminate the critical barriers to Indian power transmission system (IPTS) that were limiting the entire power service quality. Design/methodology/approach: This study uses a well-known management technique known as TOC, which has the capability and positive force to eliminate the barrier through sequential managerial procedures. TOC framework can provide practical guidance to stakeholders of the power transmission sectors through situational assessment, conflict resolution, planning and implementing changes required in the IPTS. Findings: This study explains the utility of five-steps thinking process (TP) of TOC especially in the IPTS sector. The study also describes how each step of TP can improve the performance of IPTS against its specified goal. The study brings management's attention on the system's weak links that must be leveraged by eliminating them from the system. Major types of constraints are related to the restrictive policy of the sector that mainly include lack of strategic planning, lack of investments and lesser participation of the private players in the IPTS. This study further identifies and suggests various strategies to eliminate the critical barriers of IPTS. Originality/value: The five-step process of TOC has been successfully applied in manufacturing sector and service sector processes, such as banking and medical services. This paper has uniquely applied TOC in the area of power sector, which is considered as one of key service sectors that form an important share for the Indian economy.